(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study was conducted to describe the distribution characteristics of high-sensitivity troponin I levels according to age and sex in two groups of patients with and without type 2 diabetes, thereby assessing the role of high-sensitivity troponin I in early cardiovascular complication screening and prognosis. Methods: A case-control study was conducted on 372 patients aged ≥ 18 years who visited or were admitted to Long Thanh regional General Hospital from December 2024 to June 2025, including 183 patients with type 2 diabetes and 189 patients without type 2 diabetes. Patients with a history of or current cardiovascular disease were excluded. Results: The study showed that high-sensitivity troponin I levels were significantly higher in the type 2 diabetes group compared to the non-type 2 diabetes group. The differences were statistically significant with respect to age and sex. Conclusion: Measurement of high-sensitivity troponin I is useful for early detection of cardiovascular risk in type 2 diabetes patients, even before clinical manifestations appear. However, high-sensitivity troponin I thresholds should be adjusted according to age and sex when assessing cardiovascular risk.